2016
DOI: 10.1128/aem.03464-15
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Saccharomyces cerevisiae Strains from Different Origins to Elevated Iron Concentrations

Abstract: Iron is an essential micronutrient for all eukaryotic organisms. However, the low solubility of ferric iron has tremendously increased the prevalence of iron deficiency anemia, especially in women and children, with dramatic consequences. Baker's yeast Saccharomyces cerevisiae is used as a model eukaryotic organism, a fermentative microorganism, and a feed supplement. In this report, we explore the genetic diversity of 123 wild and domestic strains of S. cerevisiae isolated from different geographical origins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Similar to the OF effect on dough rheological properties during fermentation, iron ions from lactate salt also decreased the H'm, VT, and VR values. The decrease in these values with the increase level of FE addition may be attributed to a negative effect of ions salt on the yeast cells membranes which alter their composition, especially their lipid content which is important in the maintenance of membrane fluidity and therefore yeast activity (Martinez‐Garay, Llanos, Romero, Martinez‐Pastor, & Puig, ). According to Lee et al (), iron ions may activate sphingolipid signaling and synthesis causing yeast cells toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the OF effect on dough rheological properties during fermentation, iron ions from lactate salt also decreased the H'm, VT, and VR values. The decrease in these values with the increase level of FE addition may be attributed to a negative effect of ions salt on the yeast cells membranes which alter their composition, especially their lipid content which is important in the maintenance of membrane fluidity and therefore yeast activity (Martinez‐Garay, Llanos, Romero, Martinez‐Pastor, & Puig, ). According to Lee et al (), iron ions may activate sphingolipid signaling and synthesis causing yeast cells toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…We used a colorimetric assay for the other samples (55). We previously confirmed that both methods provided similar results (51).…”
Section: Methodsmentioning
confidence: 84%
“…In order to determine yeast cellular iron concentrations as the weight of iron per yeast dry weight (grams of Fe per gram of dry yeasts), the endogenous iron levels and yeast cell dry weights of each transformant were measured after 1 day of incubation in each tested iron-containing medium (see Materials and Methods) (51). No significant differences were found for iron accumulation by ccc1⌬ cells incubated in synthetic medium with no additional iron (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such vast genomic information is facilitating the study of the mechanisms that yeasts have developed to adapt to different environments. Comparative studies have uncovered major divergences in iron metabolism among different yeast strains (Lee et al 2013;Martinez-Garay et al 2016). A phenotypic analysis of a large number of S. cerevisiae strains has shown that strains resistant to elevated iron concentrations limit iron acquisition and are sensitive to low iron conditions, whereas strains sensitive to excess iron display increased iron uptake and are better adapted to iron deficiency (Table 3; Martinez-Garay et al 2016).…”
Section: Divergence Of Iron Metabolism In Yeast Strains From Differenmentioning
confidence: 99%